SOSIALISASI MODEL PBI DALAM PEMBENTUKAN KARAKTER SISWA PEDULI KEBERSIHAN - Emelda Thesalonika; Lisbet Novianti Sihombing; Muktar B. Panjaitan; Ease Arent; Desi Sijabat (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This community service aims to provide practical guidelines for teachers in introducing and implementing the Intruduction-Based Learning Model (PBI) to shape students' characters who are concerned about cleanliness. Through a series of steps, this program presents a structured approach to introduce the PBI concept, identify cleanliness issues, design relevant learning activities, and integrate cleanliness principles into the curriculum. Additionally, the program highlights the importance of collaboration between schools and communities in raising awareness of environmental cleanliness. Through advanced training for teachers and long-term impact measurement, it is expected that this program can create sustainable changes in student behavior and environmental conditions in schools and communities. Thus, this community service makes a significant contribution to strengthening character education and cleanliness culture among students and communities